From Readiness to Performance: Modelling AI-Enabled HR Analytics Adoption Capability as a Second-Order Formative Construct in Nigerian SMEs - Michael Raphael Onenyi; Peter Ugbedeojo Nelson; Muhammed Idris Ogbike (SEISENSE (PRIVATE) LIMITED, 2026)
Objective: This study examines how AI-enabled HR Analytics Adoption Capability (AIHRA), a second-order formative construct, is associated with operational performance among Nigerian SMEs.Design: Drawing on UTAUT2, the Resource-Based View, and Socio-Technical Systems Theory, a survey was administered to 296 respondents across SMEs in Lagos, Abuja, Port Harcourt, and Kano. PLS-SEM via SmartPLS 4.0.9.9 was used for analysis.Findings: Technological Readiness (weight = 0.584, p<0.001) and Organisational Support (weight = 0.532, p<0.001) significantly form AIHRA. Perceived Value and Use is non-significant (0.119, p = 0.219) but shows absolute importance. AIHRA is positively associated with operational performance (β = 0.626, R2 = 0.392). Policy Implications: Managers and policymakers should prioritise digital infrastructure and organisational support before AI procurement. Originality: This study contributes an empirically tested higher-order formative model linking AI-HR analytics adoption capability to operational performance in Nigerian SMEs, extending prior technology-organisation-environment evidence by showing structural determinants dominate perceptual constructs within a multi-theory, capability-based specification.